A borderline range for Quantiferon Gold In-Tube results - Jonsson, Jerker; Westman, Anna; Bruchfeld, Judith; Sturegård, Erik; Gaines, Hans; Schön, Thomas (PloS one, 2017)
Interferon gamma release assays like Quantiferon Gold In-Tube (QFT) are used to identify individuals infected with Mycobacterium tuberculosis. A dichotomous cut-off (0.35 IU/ml) defines a positive QFT without considering test variability. Our objective was to evaluate the introduction of a borderline range under routine conditions. Results of routine QFT samples from Sweden (2009-2014) were collected. A borderline range (0.20-0.99 IU/ml) was introduced in 2010 recommending a follow-up sample. The association between borderline results and incident active TB within 3 to 24 months was investigated through linkage with the national TB-register. Using the recommended QFT cut-off, 75.1% tests were negative, 21.4% positive and 3.5% indeterminate. In total, 9% (3656/40773) were within the borderline range. In follow-up samples, individuals with initial results between 0.20-0.34 IU/ml and 0.35-0.99 IU/ml displayed negative results below the borderline range (<0.20 IU/ml) in 66.1% (230/348) and 42.5% (285/671) respectively, and none developed incident TB. Among 6712 individuals with a positive initial test >0.99 IU/ml, 65 (0.97%) developed incident TB within 3-24 months. We recommend retesting of subjects with QFT results in the range 0.20-0.99 IU/ml to enhance reliability and validity of the test. Half of the subjects in the borderline range will be negative at a level <0.20 IU/ml when retested and have a very low risk of developing incident active TB.